The Effect Of Marketing Knowledge Competency And Entrepreneurial Orientation On Marketing Performance Through Marketing Capability In Tempe SMEs In Situbondo Regency - Dassucik, Dassucik; Raudatul Jannah; Yudha Praja; Nindi Kamila Indawati (Jurnal Ekonomi, 2024)
Small and Medium Industries are the largest industries in Indonesia that have an important role in the Indonesian economy because they can drive economic growth and are a source of new entrepreneurial creation. Small and medium industries are expected to be more creative and prepare marketing strategies to face increasingly complex changes in the business environment. This study aims to determine the influence of marketing knowledge competency, entrepreneurial orientation, and marketing capability on marketing performance in Tempe SMEs.This study was conducted based on the gap in previous research results (research gap) and the difference in focus of discussion on entrepreneurial orientation and the influence of knowledge competence and company capabilities on marketing performance. This study was conducted by taking the object of research in Small and Medium Industries on a small scale in Situbondo City totaling 190 SMEs with new entrepreneurial elements. The sampling technique used was purposive sampling. The number of respondents determined as the research sample was 100 people. The analysis technique used to interpret and analyze the data in this study was the Structural Equation Model (SEM) technique from the AMOS software package. From the results of hypothesis testing, it is proven that the entrepreneurial orientation factor and market knowledge competence have a significant positive effect on marketing capability and marketing performance. Influence analysis is needed to determine the extent of the influence of exogenous variables on endogenous variables both directly and indirectly. The magnitude of the influence of each exogenous variable on the endogenous variable is directly apparent. entrepreneurial orientation and marketing knowledge competence there is a direct influence of entrepreneurial orientation and marketing knowledge competence on marketing capability of 0.499 and 0.281. Then there is also a direct influence on entrepreneurial orientation, marketing knowledge competence, and marketing capability of 0.353 and 0.186, and 0.555.